Writing to (Re)construct Oneself: Childhood and Youth in Maryse Condé’s Work - Álvarez Palanca, Beatriz (Thélème. Revista Complutense de Estudios Franceses, 2026)
In her autobiographical narratives, Le Cœur à rire et à pleurer (1999) and La Vie sans fards (2012), Maryse Condé retraces her identity journey from her childhood in Guadeloupe to her youth in Paris. This article offers an analysis of this vital transition through a psychological and decolonial approach. It aims to understand how time, family heritage, her conflicted relationship with her mother, motherhood, and the diasporic experience shape a complex identity in constant reconstruction. Through an unvarnished introspection, Condé deconstructs the colonial injunctions that marked her existence and ultimately asserts a hybrid identity. This process of self-decolonization is analysed here as a strategy of survival, emancipation, and self-reclamation.